PERAN DAKWAH ISLAM DALAM BUDAYA GOTONG ROYONG - Muhammad Nashrul Haqqi (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2022)
This research is to describe the role of gotong royong culture in Java as part of Islamic da'wah. The method used in this study is qualitative with a socio-cultural approach, data collection techniques through observation, interviews and documentation studies. The results show that there are two cultures of gotong royong in Java, namely social and general mutual cooperation. The culture of gotong royong among the Javanese people is the role of da'wah which is assimilated through local culture. Gotong royong contains the content to help each other, tolerance and solidarity among people